THE PECULIARITIES OF ENVY AS A COMPONENT OF CRIMINALLY ORIENTED PERSONALITY TRAITS - Zarichanskyi, Oleh; Mokhorieva, Olena; Shcherbakova, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . Envy is an emotional experience that arises in the process of social comparison and often serves as a latent driver of deviant and/or criminal behaviour. The relevance of the issue lies in the fact that envy is rarely recognised as a deep-seated motivation behind unlawful actions, yet it often accompanies a broad spectrum of socially dangerous acts. Scientific interest in envy as a constituent of criminal motives stems from the need for a more profound understanding of the emotional and motivational structure of offenders. Gender-specific manifestations of envy also warrant thorough examination, as the structure and direction of this emotion differ between males and females. The aim of this article is to present the results of an empirical study exploring the relationship between types of envy (sad envy and hostile envy) and criminal orientation in convicted male and female offenders. M e t h o d s . The following methods were employed: the personality envy diagnostic technique developed by T.V. Beskova, content analysis of judicial decisions, and statistical data processing methods (Fisher’s φ*-criterion). The sample consisted of 209 convicted individuals (N = 209) of varying ages and genders, all serving sentences for offences under the Criminal Code of Ukraine. All participants were informed of the research goals and provided informed consent. Two main subgroups were formed: those convicted of crimes against property (94 individuals) and those convicted of crimes against life and health (78 individuals); the remaining 37 individuals were excluded from comparison due to the diversity of criminal charges. R e s u l t s . Among those convicted of property crimes, high levels of sad envy were identified in 22.34 %, medium levels in 15.95 %, and low levels in 13.82 % of respondents. Hostile envy in this group was found at high levels in 10.63 %, medium in 8.51 %, and low in 14.89 %. Among those convicted of crimes against life and health, sad envy was most frequently observed at a medium level (29.48 %), followed by low (23.07 %) and high (11.53 %) levels. Hostile envy in this group had the highest share at a low level (19.23 %), with high levels observed in only 6.41 % of respondents. Statistically significant differences were found between the groups regarding the medium level of sad envy (φ = 1.702, p ≤ 0.05) and the high level of hostile envy (φ = 2.961, p ≤ 0.01). C o n c l u s i o n s . Offenders convicted of crimes against life and health are more frequently characterised by a medium level of sad envy, indicating emotional sensitivity and a sense of despair. In contrast, individuals convicted of property crimes show a higher prevalence of hostile envy, associated with aggression and animosity. Gender differences in envy experiences were also observed. The findings confirm a significant correlation between the type of envy and the criminal orientation of the individual.